SOILS OF THE DRIED PART OF THE ARAL SEA AND PROBLEMS OF DESERTIFICATION - B.R , Ramazonov; B.R , Ramazonov; R.K, Kuziev (International Journal of Psychosocial Rehabilitation, 2020)
This article deals with the specific soil formation conditions of the dried part of the Aral Sea, as well as the agrochemical and other properties of semi-automorphic, semi-hydromorphic coastal solonchaks and desert-sandy soils.